2007
DOI: 10.1080/02841850701367911
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and core needle biopsy in the differential diagnosis of fibroadenoma and tumor phyllodes

Abstract: Imaging-guided core needle biopsy was accurate in differentiating between fibroadenomas and phyllodes tumors. US classification was unreliable due to considerable overlap in the findings. Combined use of US feature analysis and needle biopsy may help to avoid the misinterpretation of phyllodes as fibroadenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
50
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 23 publications
12
50
1
8
Order By: Relevance
“…highest among all relevant studies. Choi (12) reported that among 129 patients having undergone preoperative CNB diagnosis, 104 were verified by postoperative pathology, yielding an accuracy rate of 80.6%, similar to the results of Bode et al (11). In addition, Komenaka et al (22) and Ward et al (17) reported accurate CNB diagnostic rates of 76.0% and 63.0%.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…highest among all relevant studies. Choi (12) reported that among 129 patients having undergone preoperative CNB diagnosis, 104 were verified by postoperative pathology, yielding an accuracy rate of 80.6%, similar to the results of Bode et al (11). In addition, Komenaka et al (22) and Ward et al (17) reported accurate CNB diagnostic rates of 76.0% and 63.0%.…”
Section: Discussionsupporting
confidence: 73%
“…Bolívar et al (26) proposed obtaining a minimum of three specimens via ultrasound-guided CNB for cases of breast tumors that were difficult to examine via palpation. Bode et al (11) reported that using 14 G or 16 G biopsy needles could deliver a relatively improved outcome in differentiating a PTB specimen from that of FA. Although 14 G needles were used in this study, only 1 specimen was obtained from each breast tumor patients, which might explain the relatively low rate of accurate CNB diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients older than 50 to 55 years are more likely to have a phyllodes tumor (7). In the present study, age was not a useful discriminant, unlike other studies (2,4,9). This finding may be explained by the fact that a surgical excision was usually performed in older patients at our institution if an initial CNB revealed a fibroepithelial lesion, regardless of other features suggestive of a fibroadenoma.…”
Section: Discussioncontrasting
confidence: 56%
“…older than patients with fibroadenomas (1,4,9). Patients older than 50 to 55 years are more likely to have a phyllodes tumor (7).…”
Section: Discussionmentioning
confidence: 99%